'At the end of the day, it is more important that he stays happy': an interpretative phenomenological analysis of people who have a sibling with 22q11.2 deletion syndrome. Issue 9 (September 2017) - Goodwin, J.; Alam, S.; Campbell, L. E.
Abstract: Background: 22q11.2 deletion syndrome (22q11.2DS) is the most common microdeletion syndrome. However, there is little research examining the effect of this multisystem disorder on the family, particularly siblings. The current study was a phenomenological exploration of sense‐making in siblings of a person with 22q11.2DS. Method: Interpretative phenomenological analysis informed a detailed and open examination of being a sibling of a person with 22q11.2DS. Using in‐depth semistructured interviews, five typically developing siblings (two men, three women) of people with 22q11.2DS were individually interviewed, providing the data set for transcription and thematic analysis. Results: The theme ' They are the priority ' overarched two subordinate themes that emerged from participants' descriptions of the struggle with acceptance and finding positive meaning. Participants oscillated between conflicting feelings about their sibling with 22q11.2DS always taking centre stage. For example, they felt anger, guilt and resentment; yet, they also embraced patience, empathy and gratitude. Conclusions: This phenomenological study provides a foundation for future research relating to 22q11.2DS and fostering family wellbeing, particularly around acceptance and psychological growth. The siblings in this study actively withdrew from their family to allow prioritisation of their affected sibling. However, this does not mean that their needs should be overlooked. There are easily accessible resources to support siblings of individuals with disabilities, and it is important for health professionals and parents to consider these options.